Analisis Pengaruh ESG Terhadap Kinerja Keuangan Perusahaan Dengan Transformasi Digital Sebagai Variabel Pemoderasi - Regina Putri Heryana; Harry Z. Soeratin (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This research examines the relationship between Environmental, Social, and Governance (ESG) implementation and corporate financial performance, with digital transformation as a moderating variable. In an increasingly complex digital era, the integration of ESG with digital technology has become a crucial factor in determining company success and sustainability. Through a qualitative approach with library research methods, this study analyzes various academic and professional literature sources during the 2014-2024 period. The results show that companies with effective ESG implementation achieve operational efficiency improvements of up to 20%, while the integration of digital technology in ESG implementation increases efficiency by up to 30% compared to conventional approaches. The use of technologies such as Internet of Things, blockchain, and artificial intelligence in ESG management results in 60% faster and more accurate risk identification. Sectoral analysis reveals significant impact variations, with the manufacturing sector recording a 30% increase in operational efficiency, the financial services sector experiencing a 25% increase in customer satisfaction, and the energy sector showing 35% higher revenue growth for sustainable portfolios. This research provides theoretical and practical contributions to understanding the role of digital transformation as a catalyst for ESG implementation and improving corporate financial performance.